Synthesis, characterization and antibacterial activity of imidazole derivatives of 1,10-phenanthroline and their Cu(II), Co(II) and Ni(II) complexes - Gomleksiz, Mesut; Alkan, Cihan; Erdem, Belgin (My University, 2013)
Six new CuL1 (L1 = 4-bromo-2-(1H-imidazo[4,5-f][1,10] phenanthroline-2-yl)phenol), CoL1, NiL1, CuL2 (L2 = 2-(1H-imidazo[4,5-f] [1,10]phenanthroline-2-yl)-5- methoxyphenol), CoL2 and NiL2 complexes were synthesized. L1 and L2 ligands were prepared by the condensation of 1,10-phenanthroline-5,6-dione with 5-bromosalicylaldehyde and 2-hydroxy-4-methoxybenzaldehyde, respectively. The structures of the compounds were determined by elemental analyses, IR,UV-visible, 1H-NMR, TGA, magnetic susceptibilities and molar conductance measurements. It is observed that the synthesized complexes have tetragonal and distorted square pyramidal geometrical structures. Antibacterial activity of the ligands and their metal complexes were tested against selected bacteria by disc diffusion method.
Keywords: 1-10-Phenanthroline; Antibacterial activity; Complex; Imidazole